Capacity Demands in Short-Term Memory for Synthetic and Natural Speech - LUCE, PAUL A. (1983)
Three experiments were performed that compared recall for synthetic and natural lists of monosyllabic words. In the first experiment, presentation intervals of 1, 2, and 5 s per word were used. Although free recall was consistently poorer overall for the synthetic lists at all presentation rates, the decrement for synthetic stimuli did not increase differentially with faster rates. In a second experiment, zero, three, and six digits were presented visually for retention prior to free recall of each spoken word list in a preload paradigm. Fewer subjects were able to correctly recall all of the digits for the six-digit list than the three-digit list when the following word lists were synthetic. The third experiment required ordered recall of lists of natural and synthetic words. Differences in ordered recall between the synthetic and natural word lists were substantially larger for the primacy portion of the serial position curve than the recency portion. These results indicate that difficulties observed in the perception and comprehension of synthetic speech are due, in part, to increased processing demands in short-term memory.